A felicidade em protocolos de comunicação: práticas midiáticas e formas de vida - Witzki, Fabio Luiz (2018)
Happiness is the understanding and the feeling most desired and idealized by people since the genesis of society. Since of antiquity, a theoretical perspective demonstrated the concern about discovering what it is and how to reach the state of happiness. Are emphasized some thoughts historically focused on this phenomenon and its imperatives that are seen in communication processes in the present day. In Ancient Greece Aristoteles, Epicteto and Epicuro thought Politics emphasizes know about men, on man’s virtue, his life in society and how to be happy in it. Nowadays concepts about happy life on Sociology by Gilles Lipovetsky are resonating throughout paradox in the search for happiness in a society of hyperconsumption. Pascal Bruckner, however, discusses his work and shows the feeling related to a state of perpetual euphoria. João Freire Filho, in turn, relates the feeling between the moving forces of contemporary. As Philosophy and Sociology are the main points of thesis with of certain key concepts about happiness and actual society, communication is revealing in the other hands like an ambient where discuss happens, so, we get another theoretical background its send to communication process and key features like interdisciplinary by José Luiz Braga, convergence by Henry Jenkins and substantial changing in the communication processes and its contemporary lifestyle, how it’s showed by Muniz Sodré. In this way, I’ve intended to observe how the focus on the sense of happiness in the communication process that it’s giving rise to one (or more) discursive manifestations of feeling. Our methods observe Discursive Semiotic by Greimas and searches from theoretical and methodically of the author, as well as the perspective about Aesthetic of communication and Studies of the Discourse The corpus of the research is broad and divided into four thematic groups: consumption, health and wellness, spatiality and ordinary and within this semantic framework, the examples will be distributed. The initial and final chapters of the thesis present respectively the relation of happiness and communication with the issues of the contemporary, as well as the way the discourses assume a discursive configuration. At these specific times, other examples will be called for figurative titles. The results point to the perspectives that end up resembling the assertion that the communicative signs are semiotic, aesthetic and synesthetic mean of a "generative trajectory of happiness".